(untitled) (Journal of Naval Architecture and Marine Engineering, 2017)
This paper deals with unsteady oscillatory flow of viscous incompressible fluid with heat & mass transfer in a horizontal channel partially occupied by porous medium following the Darcy-Brinkman model. The interior territory of the channel consists of two regions; one of them is filled with porous material and second is clear fluid. At the porous medium fluid interface, interfacial coupling conditions for the fluid velocity, temperature and concentration were used to derive the analytical solution. The effects of pertinent physical fluid parameter like porosity, viscosity ratio, density ratio etc. on velocity, temperature and concentration distribution are considered and demonstrated through graphs. Also, the non-dimensional Skin-friction coefficient, Nusselt number and Sherwood number have been calculated and reported in tabular form.